Hakikat pendidikan Islam dalam perspektif Esensialisme: Peran guru, kurikulum, dan relevansinya terhadap pembentukan karakter peserta didik muslim diera modern - Akbar Muhammad Farizi; Abdul Khobir; Etika Yuliana; Naila Zulfa Nabila (Jurnal Pendidikan Agama Islam, 2026)
This article discusses the philosophical relationship between essentialism and Islamic education, especially in forming the moral character of Muslim students in the modern era. The study analyzes three main aspects: (1) the essence of Islamic education in the view of essentialism; (2) the role of teachers and curriculum as carriers of essential values; and (3) the relevance of essentialist principles for strengthening Islamic character education in contemporary times. Using literature review methods, this article concludes that essentialism is relevant to Islamic education because both emphasize discipline, moral stability, and mastery of fundamental knowledge. Teachers act as murabbi and moral exemplars, while the curriculum becomes the guardian of essential Islamic values to balance intellectual, moral, and spiritual development. The study proposes a conceptual model of “Essentialist Islamic Character Education” integrating essentialist philosophy with Islamic moral principles to answer modern educational challenges.